2015
DOI: 10.1097/dbp.0000000000000222
|View full text |Cite
|
Sign up to set email alerts
|

Early Emergence of Delayed Social Competence in Infants Born Late and Moderately Preterm

Abstract: Birth at 32 to 36 weeks of gestation confers a specific risk for delayed social competence at 2 years of age. This may be indicative of an increased risk for psychiatric disorders later in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 30 publications
8
30
0
Order By: Relevance
“…This indicates that socioeconomic factors may play an increasingly important role compared with birth and medical history in a child's academic performance as he or she ages 7 17. These results are consistent with previous publications that have found a strong link between SES and cognitive outcomes in NICU-admitted children and children with neurological complications, with supplanting or amplifying effects of SES on complications of lower gestational age at birth 1 14 19–21 25 26…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This indicates that socioeconomic factors may play an increasingly important role compared with birth and medical history in a child's academic performance as he or she ages 7 17. These results are consistent with previous publications that have found a strong link between SES and cognitive outcomes in NICU-admitted children and children with neurological complications, with supplanting or amplifying effects of SES on complications of lower gestational age at birth 1 14 19–21 25 26…”
Section: Discussionsupporting
confidence: 90%
“…In some studies, these social factors have been shown to be more important predictors of cognitive outcomes, especially as a child ages, than prematurity or medical complications 7 10 14 19–21…”
Section: Introductionmentioning
confidence: 99%
“…At 24 months' corrected age, parents completed a questionnaire that comprised validated scales to identify children with cognitive impairment, 14 language delay, 14 behavioral problems, 8 delayed socioemotional competence, 8 autism spectrum symptoms, 15 and eating difficulties. 9 The Parent Report of Children's Abilities-Revised (PARCA-R) 16 was used to assess cognitive and language development.…”
Section: Methodsmentioning
confidence: 99%
“…These parents are in a state of “premature parenting” in which the transition to parenthood takes place ahead of its time (Stern, ). Furthermore, prematurely born infants are less engaged and responsive in dyadic interactions compared to full‐term infants (e.g., De Schuymer et al., ; Johnson et al., ), suggesting that preterm infants can be more challenging interaction companions for parents. Extensive research indicates that parents of preterm infants are more prone to distress compared to parents of full‐term infants: They often experience a sense of loss of the parental role as well as a decrease in confidence as parents during the hospitalization of their newborn, and they suffer more from anxiety, parental stress, posttraumatic stress symptoms, and depression, especially in the first months postpartum (e.g., Al Maghaireh, Abdullah, Chan, Piaw, & Al Kawafha, ; Miles & Holditch‐Davis, ; Olshtain‐Mann & Auslander, ; Poehlmann et al., ; Suttora, Spinelli, & Monzani, ).…”
Section: Maternal Mentalization and Behaviors During Observed Dyadic mentioning
confidence: 99%